La faute et son ralenti. Le cadrage temporel et visuel de l’action normée - Laurent Camus (Temporalités)
In this paper, we examine the reflexive link between the temporal unfolding of a sports game and its broadcasting live on TV. Borrowing from a video-ethnography in the control-room of technicians producing video football matches in real-time, this article aims to study how professionals deal with the time-out pauses and the interruptions during a match. Those interruptions, generally triggered by the referee’s whistle, constitute a practical problem for TV broadcasting. When the game is stopped, actions that then take place are not directly controlled by the rules of the game but the broadcasters need to show something to the spectators. A micro-analysis of the interaction demonstrates how the referee’s whistle creates a transition towards slow-motion sequences, i.e. filmed actions allowing one to see an event under a new angle. Thus an element of the game is re-used as a temporal and descriptive resource in the on-going activity of broadcasting.